Decadal Changes in the Annual Growth of Two Commercial Ommastrephid Species in the Pacific Ocean - Peiwu Han; Jianhua Li; Yating Dan; Bilin Liu; Xinjun Chen; Zhou Fang (Fishes, 2022)
Neon flying squid Ommastrephes bartramii and jumbo flying squid Dosidicus gigas are two important commercial ommastrephid species in the Pacific Ocean. As short-lived marine species, squids are highly susceptible to changes in climate and marine environments. According to samples collected from the northwest and southeast Pacific Ocean in different years, we explored the growth characteristics of these two squids in terms of their mantle length (ML) distribution and the relationship between mantle length and body weight (LWR), also considering the relative condition factors (Kn), and explored the effects of the El Niño and Southern Oscillation (ENSO) on their growth. The results showed that the ML for O. bartramii and D. gigas had significant differences among different years and different sexes (p 3), and parameters a and b were influenced by year and sex. Furthermore, there were significant differences in Kn in both squids for different years and different sexes (p